A Festa Inacabada A implantação do Centro de Lançamento de Alcântara e a constituiçao de sujeitos liminares - ROCHA, Ana Tereza Ferreira (2007)
The present dissetation is fruit of research carried through in the city of Alcântara, more necessarily in agrovila Peptal and deals with the obligatory transformation of a campesinato of use joint in parceling out, from the implantation of the Center of Launching of Alcântara. Such transformation generated a economic disaggregation of segments peasants who occupied ancestrally its old lands, sharing values paved in ethnic principles. Taking as reference the information gotten by means of practical interviews and comment of the social ones of the studied group, apprehended by means of etnography research, the work aims at to analyze, in this context, the events that had compulsively marked the life of the families transferred to agrovila Peptal as well as its constitution as preliminary citizens throughout more than two decades of existence of the Center of Launching of Alcântara.